Incidental findings on temporal bone computed tomography - Zeynep Nilufer Tekin; Mehmet Bilgin Eser; M. Tayyar Kalcioglu (Medicine Science, 2022)
The aim of this study was to describe the prevalence of incidental findings in the temporal bone computed tomography (CT) images. The temporal bone CT scans of 130 patients (69 females and 61 males; mean age: 38.2 years) with a clinical indication for potential temporal diseases were re-evaluated for incidental extratemporal findings by two experienced radiologists. Demographic and radiological data were collected for each patient. A total of 780 incidental extratemporal findings were noted in 129 of 130 patients (99.2%). Incidental extratemporal findings were classified into 9 location groups: intracranial intra-axial, vascular, intracranial extra-axial, bone, lymph node, sinus, nasal cavity, nasopharynx and tonsillar pathologies. Nasal cavity and sinus pathology were the most frequent incidental findings with a rate of 68.5%. Nasal septum deviation (65.4 %) was the most common incidental finding and inferior turbinate hypertrophy was next in frequency (55.4 %). Since incidental extratemporal findings are detected in high frequency (99.2%) in temporal bone CT, all the adjacent anatomical structures should also be evaluated in temporal bone imaging to prevent misdiagnosis and to avoid malpractices by radiologists and otolaryngologists. Although the identification and follow-up of incidental findings are parallel to the clinical significance of lesions, this evaluation is necessary to prevent underdiagnosis that may affect patient's treatment and may even rarely be life-threatening. [Med-Science 2022; 11(2.000): 740-4]